Análise estrutural e bioquímica da hidroxiapatita submetida ao tratamento com fluoreto e polifosfatos - Amaral, Jackeline Gallo do [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study evaluated the effect of sodium trimetaphosphate (TMP) and sodium hexametaphosphate (HMP) associated or no with fluoride (F) on the structure and dissolution of hydroxyapatite (HA). For this purpose, the study was divided into three subprojects. In Subprojects 1 and 2, synthetic HA powder (n=6) was treated with solutions containing TMP varying at 0-10% associated with 0, 100, 250, 500 (Subproject 1) and 0, 1100, 4500 and 9000 ppm F (Subproject 2) and submitted to a pH cycle. Afterwards, alkali- and acid soluble F, Ca and P were determined in/on HA, and P and F in the supernatants. Samples were analyzed by infrared spectroscopy (FTIR), X-ray diffraction (XDR) and energy-dispersive X-ray spectroscopy (EDX). In Subproject 3, HA discs were used to assess the dissolution rate of HA using a pHstat system. HA discs were treated with 1100 ppm F, 1% and 8% of HMP or TMP and 1100 ppm F associated with 1% and 8% of HMP or TMP, totaling 9 groups (n=8). The influence of a salivary pellicle on HA dissolution was also assessed. HA discs were kept in pooled human saliva before treatment with deionised water and 1100 ppm F associated with 1% and 8% of HMP or TMP, totaling 5 groups (n=8). The post-treatment dissolution rate was determined from three consecutive 30-min assays. Data were submitted to ANOVA, Student-Newman-Keuls' test and Pearson's correlation coefficient (Subprojects 1 and 2), and to ANOVA and Fisher and Holm- Sidak methods (Subproject 3) (α=0.05). Ca/P ratios values were higher for the fluoride solutions when compared with the no F and TMP groups and dependent of the F:TMP ratio used (p<0.05). The overall trend was that alkali-soluble F deposition was directly related to TMP concentrations in the treatment solutions, while acidsoluble incorporation was inversely related to TMP...

Este estudo avaliou o efeito do trimetafosfato de sódio (TMP) e hexametafosfato de sódio (HMP) associados ou não ao fluoreto (F) na dissolução e estrutura da hidroxiapatita (HA). Para tanto, o estudo foi dividido em três subprojetos. Nos subprojetos 1 e 2, o pó de HA sintética (n=6) foi tratado com soluções contendo entre 0 e 10% de TMP associado a 0, 100, 250, 500 (Subprojeto 1) e a 0, 1100, 4500 e 9000 ppm F (Subprojeto 2), sendo submetido a um ciclo de pH. As concentrações de F alcáli- e ácido solúvel, cálcio (Ca) e fósforo (P) foram determinadas na HA, e as de P e F no sobrenadante. As amostras foram analisadas pela espectroscopia no infravermelho (FTIR), difração de Raios-X (DRX) e espectroscopia de energia dispersiva (EDX). No Subprojeto 3, discos de HA foram empregados para avaliar a taxa de dissolução da mesma utilizando o sistema pHstat. Estes foram tratados com soluções contendo 1100 ppm F, 1 e 8% de HMP ou TMP e 1100 ppm F associado com 1 e 8% de HMP ou TMP, totalizando 9 grupos (n=8). A influência da película salivar também foi avaliada. Discos de HA foram mantidos em saliva humana previamente ao tratamento com água deionizada e 1100 ppm F associado com 1 e 8% de HMP ou TMP, totalizando 5 grupos (n=8). A taxa de dissolução pós-tratamento foi determinada a partir de 3 medidas consecutivas a cada 30 min. Os dados foram submetidos a ANOVA, teste de Student-Newman-Keul's e coeficiente de correlação de Pearson (Subprojetos 1 e 2) e a ANOVA e testes de Fisher e Holm-Sidak (Subprojeto 3) (α=0,05). Valores de proporção Ca/P maiores foram observados para as soluções fluoretadas quando comparados à solução sem F e TMP, sendo os mesmos dependentes da proporção F:TMP (p<0,05). A deposição do F álcali-solúvel foi diretamente relacionada com as concentrações de TMP nas soluções...
Keywords: Polifosfatos; Fluoretos; Saliva; Durapatita; Polyphosphates